2004
DOI: 10.1186/1471-2202-5-39
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Tasks involving conflict are widely used to study executive attention. In the flanker task, a target stimulus is surrounded by distracting information that can be congruent or incongruent with the correct response. Developmental differences in the time course of brain activations involved in conflict processing were examined for 22 four year old children and 18 adults. Subjects performed a child-friendly flanker task while their brain activity was registered using a high-density electroencephalogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
114
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 31 publications
15
114
1
1
Order By: Relevance
“…However, the averaged conflict scores at posttest were smaller and more adult-like for the trained group at both ages than for their controls. The posttraining score for 6-year-olds (39 ms) is rather similar to adult scores (30 ms) for this task (21). The training effect overall was about half as large as the one due to the 2 years of development from 4 to 6 years of age (see Table 4).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the averaged conflict scores at posttest were smaller and more adult-like for the trained group at both ages than for their controls. The posttraining score for 6-year-olds (39 ms) is rather similar to adult scores (30 ms) for this task (21). The training effect overall was about half as large as the one due to the 2 years of development from 4 to 6 years of age (see Table 4).…”
Section: Discussionsupporting
confidence: 57%
“…Electrophysiological data served to investigate changes in the pattern of brain activations due to training. According to previous studies with the same and similar flanker tasks, conflict-related effects were most expected around the N2 component for channels located at frontoparietal and prefrontal areas (21,22). In addition, results from adult studies have shown that the fronto-parietal N2 reflects conflict-related activity in the anterior cingulate (22).…”
Section: Resultsmentioning
confidence: 64%
“…In these studies it is usually shown that adolescents typically exhibit increased error rates, RTs and N2 amplitudes (Ladouceur et al, 2007;Ridderinkhof et al, 1997;Ridderinkhof and van der Molen, 1995;Rueda et al, 2004). Similar results were obtained in this study, even though superimposed by higher order interactions of "transition" and "predictability", which are broadening the perspective of conflict monitoring.…”
Section: Discussionsupporting
confidence: 90%
“…As recently suggested, the successful performance of this selective attention task depends not only on the alerting and orienting networks but also on the facilitating effect of the orienting cues when conflict resolution is required [53,54]. In this perspective, one could postulate that MCI participants with single dysexecutive deficits need more time for the activation of cortical circuits that subserve conflict resolution compared to other MCI subgroups [26,55]. Alternatively, the increased P300 latency could be attributed to the allocation of additional neural resources necessary for the successful performance of the cognitive task in this diagnostic group.…”
Section: Discussionmentioning
confidence: 99%